2022
DOI: 10.1038/s41390-021-01929-1
|View full text |Cite
|
Sign up to set email alerts
|

ADHD symptoms and diagnosis in adult preterms: systematic review, IPD meta-analysis, and register-linkage study

Abstract: Background This study examined differences in ADHD symptoms and diagnosis between preterm and term-born adults (≥18 years), and tested if ADHD is related to gestational age, birth weight, multiple births, or neonatal complications in preterm borns. Methods (1) A systematic review compared ADHD symptom self-reports and diagnosis between preterm and term-born adults published in PubMed, Web of Science, and PROQUEST until April 2021; (2) a one-stage Individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 44 publications
3
15
1
5
Order By: Relevance
“…Increased psychiatric morbidity from 14 years to 19 and 26 years is in line with two comprehensive meta‐analyses in the APIC consortium, showing long‐term consequences of being born preterm with VLBW into adulthood, especially internalising problems, 5 anxiety and mood disorders, attention deficit hyperactivity and autism spectrum disorders 6 . The increased risk of attention deficit hyperactivity disorder is also supported by a recent publication that includes register data from Finland 74 . A large multinational cohort study using data from several Nordic registers has documented an increased risk of autism spectrum disorder for each week of decreasing gestation from week 40 to week 24 75 …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Increased psychiatric morbidity from 14 years to 19 and 26 years is in line with two comprehensive meta‐analyses in the APIC consortium, showing long‐term consequences of being born preterm with VLBW into adulthood, especially internalising problems, 5 anxiety and mood disorders, attention deficit hyperactivity and autism spectrum disorders 6 . The increased risk of attention deficit hyperactivity disorder is also supported by a recent publication that includes register data from Finland 74 . A large multinational cohort study using data from several Nordic registers has documented an increased risk of autism spectrum disorder for each week of decreasing gestation from week 40 to week 24 75 …”
Section: Discussionsupporting
confidence: 75%
“…6 The increased risk of attention deficit hyperactivity disorder is also supported by a recent publication that includes register data from Finland. 74 A large multinational cohort study using data from several Nordic registers has documented an increased risk of autism spectrum disorder for each week of decreasing gestation from week 40 to week 24. 75 Our finding of reduced expiratory airflow of the lungs is confirmed by a meta-analysis of individual participant data in the APIC consortium, where the mean difference was −0.78SD between the very preterm/VLBW (n = 935) and control participants (n = 722).…”
Section: Body Functions and Structuresmentioning
confidence: 99%
“…Nevertheless, both individual participant data meta-analyses and a registry-linkage study have reported a higher prevalence of ADHD. 5,6 The lack of significant differences between the VLBW and control group regarding peer relationship problems and prosocial behaviour contradicts previously published results. Poor social functioning of adults born preterm has been reported in terms of deficits in romantic partnership and self-reported poorer relationship with friends.…”
Section: Consistency With Literaturecontrasting
confidence: 56%
“…However, it should be noted, as pointed out as a limitation, that the SDQ combines hyperactivity and inattention and includes this in the externalising problems scale, while attention problems are not part of the ASEBA ASR externalising scale. Nevertheless, both individual participant data meta‐analyses and a registry‐linkage study have reported a higher prevalence of ADHD 5,6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation